A study on the correlation of environmental consciousness and policy in a private enterprise - YANAGAWA, Tomonori; SASATANI, Yasuyuki; HIRAI, Koji; KOMORI, Masaya (ENVIRONMENTAL SYSTEMS RESEARCH, 1999)
Private citizens, industry and government must seek ways to each carry out its own decisive policies, especially industry, which is driven by economic concerns, must strive to implement its own aggressive environmental policies. Kiko Network, Environmental Non-Government-Organization, have researched about the consciousness and policy the rate of operation for 509 companies. To reach this goal our research shows that the possibility for advancing environmental policy is most hopeful when industry works together in partnership with Non Government Organizations to provide incentive to implement environmental protection policy.